Congenitally corrected transposition with left ventricular outflow obstruction and cardiac malposition: One-and-a-half ventricular repair vs. Fontan pathway? - Liu, Rui; Pang, Kunjing; Rui, Lu; Zhang, Benqing; Wang, Chao; Li, Shoujun (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This study was to assess the mid-term results of the one-and-a-half ventricular repair (hemi-Mustard and bidirectional Glenn procedures combined with the Rastelli procedure) and Fontan pathway for correcting congenitally corrected transposition of great artery (ccTGA) patients with left ventricular outflow tract obstruction (LVOTO) and cardiac malpostion. Methods: At this retrospective study, 74 consecutive ccTGA with LVOTO and cardiac malpositon underwent the one-and-a-half ventricular repair (group A; 33 cases) and Fontan operation (group B; 41 cases) between October 2011 and March 2018. Median follow-up time are 49 (20-84) and 42 (7-85) months in group A and B. To estimate excise tolerance the 6minute walk test (MWT) was performed. Results: No in-hospital death. Compared with group A, group B have significant less CPB, mechanical ventilation time and intensive care unit stay, but prolonged pleural effusions developed more frequently in the Group B. The survival probability were 90.2% (95% CI, 80.2%-100%) and 97.2% (95% CI, 92%-100%) at 7 years (p=0.300) in group A and B. The probability of freedom from re-intervention were 80.6% (95% CI, 66.5%-97.6%) and 97.2% (95% CI, 92%-100%) at 7 years (p=0.110). Longitudinal repeated measured echo data at every follow-up time shows that group A have more systemic ventricular EF% (p<0.001) and less moderate systemic ventricular valve regurgitation (p<0.001) compared with group B. Estimated by 6 MWT, group A has better outcomes for six-minute walk distance . Conclusions: For correction of ccTGA with LVOTO and cardiac malposition, the one-and-a-half ventricular repair had superior midterm heart function and excise tolerance.